Physical performance changes during circuit training and detraining in U15 soccer players - Vianna, L.; Marques, D. L.; Marques, M. C.; Ferraz, R. (Journal of Human Sport & Exercise, 2020)
On-field soccer conditioning programs are effective to improve physical performance in soccer players. However, the effects of an in-season soccer-specific circuit during regular soccer training is still limited. Thus, this study aimed to analyse the effects of a soccer-specific circuit, followed by 4-weeks of detraining on physical performance in U15 soccer players. Twenty participants (13.3 ± 0.5 years) were involved in this study. A soccer-specific circuit (~15-min) performed without ball was applied three times per week and included sprints, changes of direction, jumps and skipping`s. Before and after 6-weeks, as well as after detraining, the outcome measures included: countermovement jump, repeated sprint ability, yo-yo intermittent recovery test level 1, change of direction and the 300-m modified shuttle-run test. After 6-weeks, repeated measures ANOVA revealed significant gains (p < .05) in almost variables, except for the percent sprint decrement in the repeated sprint ability test. After detraining, significant decreases (p < .05) were observed in almost variables, except for the countermovement jump best height and the repeated sprint ability best time. The results demonstrated that an in-season soccer-specific circuit was effective to improve physical performance in U15 soccer players. Nonetheless, 4-weeks of detraining is enough to revert the positive training-induced adaptations.